Two-stage laparoscopic transversus abdominis plane block as an equivalent alternative to thoracic epidural anaesthesia in bowel resection: an explorative cohort study - Kaufmann, Mario; Orth, Vanessa; Dorwarth, Tim-Janick; Benrath, Justus; Gerber, Benjamin; Ghezel-Ahmadi, D.; Reißfelder, Christoph; Herrle, Florian (International journal of colorectal disease, 2024)
Purpose: We evaluated the effect of the two-stage laparoscopic transversus abdominis plane block (TS-L-TAPB) in comparison to thoracic epidural anaesthesia (TEA) and a one-stage L-TAPB (OS-L-TAPB) in patients who underwent elective laparoscopic bowel resection. Methods: We compared a TS-L-TAPB (266 mg bupivacaine), which was performed bilaterally at the beginning and end of surgery, with two retrospective cohorts. These were patients who had undergone a TEA (ropivacaine/sufentanil) or an OS-L-TAPB (200 mg ropivacaine) at the beginning of surgery. Oral and i.v. opiate requirements were documented over the first 3 postoperative days (POD). Results: Patients were divided into three groups TEA (n = 23), OS-L-TAPB (n = 75), and TS-L-TAPB (n = 49). By the evening of the third POD, patients with a TEA had a higher cumulative opiate requirement with a median of 45.625 mg [0; 202.5] than patients in the OS-L-TAPB group at 10 mg [0; 245.625] and the TS-L-TAPB group at 5.625 mg [0; 215.625] (p = 0.1438). One hour after arrival in the recovery room, significantly more patients in the TEA group (100%) did not need oral and i.v. opioids than in the TS-L-TAPB (78%) and OS-L-TAPB groups (68%) (p = 0.0067).This was without clinical relevance however as the median in all groups was 0 mg. On the third POD, patients in the TEA group had a significantly higher median oral and i.v. opioid dose at 40 mg [0; 80] than the TS-L-TAPB and OS-L-TAPB groups, both at 0 mg [0; 80] (p = 0.0009). Conclusion: The TS-L-TAP showed statistically significant and clinically meaningful benefits over TEA and OS-L-TAP in reducing postoperative opiate requirements.